Patient-Level Discordance in Population Percentiles of the Total Cholesterol to High-Density Lipoprotein Cholesterol Ratio in Comparison With Low-Density Lipoprotein Cholesterol and Non–High-Density Lipoprotein Cholesterol. Issue 8 (25th August 2015) - Elshazly, Mohamed B.; Quispe, Renato; Michos, Erin D.; Sniderman, Allan D.; Toth, Peter P.; Banach, Maciej; Kulkarni, Krishnaji R.; Coresh, Josef; Blumenthal, Roger S.; Jones, Steven R.; Martin, Seth S.
<x xml:space="preserve">Abstract</x> Background— The total cholesterol to high-density lipoprotein cholesterol (TC/HDL-C) ratio, estimated low-density lipoprotein cholesterol (LDL-C), and non–HDL-C are routinely available from the standard lipid profile. We aimed to assess the extent of patient-level discordance of TC/HDL-C with LDL-C and non–HDL-C, because discordance suggests the possibility of additional information. Methods and Results— We compared population percentiles of TC/HDL-C, Friedewald-estimated LDL-C, and non–HDL-C in 1 310 432 US adults from the Very Large Database of Lipids. Lipid testing was performed by ultracentrifugation (Vertical Auto Profile, Atherotech, AL). One in 3 patients had ≥25 percentile units discordance between TC/HDL-C and LDL-C, whereas 1 in 4 had ≥25 percentile units discordance between TC/HDL-C and non–HDL-C. The proportion of patients with TC/HDL-C > LDL-C by ≥25 percentile units increased from 3% at triglycerides <100 mg/dL to 51% at triglycerides 200 to 399 mg/dL. On a smaller scale, TC/HDL-C > non–HDL-C discordance by ≥25 percentile units increased from 6% to 21%. In those with <15th percentile levels of LDL-C (<70 mg/dL) or non–HDL-C (<93 mg/dL), a respective 58% and 46% were above the percentile-equivalent TC/HDL-C of 2.6. Age, sex, and directly measured components of the standard lipid profile explained >86% of the variance in percentile discordance between TC/HDL-C versus LDL-C and non–HDL-C. Conclusions— In this contemporary, cross-sectional, big data analysis of US adults who underwent advanced lipid testing, the extent of patient-level discordance suggests that TC/HDL-C may offer potential additional information to LDL-C and non–HDL-C. Future studies are required to determine the clinical implications of this observation. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01698489.